La opinión pública medida y mediatizada. La comunicación social en la España democrática - Vinuesa Tejero, María Lourdes (Estudios sobre el Mensaje Periodístico, 2008)
This article is about the history of the concept of “public opinion” during the last three decades of democratic period in Spain (1976-2008). Our approach focus on the concepts of public opinion we can find published in the mass media because we emphasise that mass media create and develop different concepts of public opinion. We analyze the role of the press to build a new political culture to support democracy and what can be the mass media tasks in order to empower the political culture and democracy.